GmPGL1, a Thiamine Thiazole Synthase, Is Required for the Biosynthesis of Thiamine in Soybean - Feng, Xingxing; Yang, Suxin; Tang, Kuanqiang; Zhang, Yaohua; Leng, Jiantian; Ma, Jingjing; Wang, Quan; Feng, Xianzhong (Frontiers in Plant Science, 2019)
Thiamine is an essential cofactor in several enzymatic reactions for all living organisms. Animals cannot synthesize thiamine and depends on their diet. Enhancing the content of thiamine is one of the most important goals of plant breeding to solve the thiamine deficiency associated with the low-thiamin staple crops. In this study, a Glycine max pale green leaf 1 (Gmpgl1) mutant was isolated from the EMS mutagenized population of soybean cultivar, Williams 82. Map-based cloning of the GmPGL1 locus revealed a single nucleotide deletion at the 292th nucleotide residue of the first exon of Glyma.10g251500 gene in Gmpgl1 mutant plant, encoding a thiamine thiazole synthase. Total thiamine contents decreased in both seedlings and seeds of the Gmpgl1 mutant. Exogenous application of thiazole restored the pale green leaf phenotype of the mutant. The deficiency of thiamine in Gmpgl1 mutant led to reduced activities of the pyruvate dehydrogenase (PDH) and pyruvate decarboxylase (PDC), and decreased contents of six amino acids as compared to that in the wild type plants. These results revealed that GmPGL1 played an essential role in thiamine thiazole biosynthesis.